2018
DOI: 10.4236/msa.2018.912068
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Thermodynamic Properties of Zirconia Thin Films by Statistical Moment Method

Abstract: The moment method in statistical (SMM) dynamics is used to study the thermodynamic quantities of ZrO 2 thin films taking into account the anharmonicity effects of the lattice vibrations. The average lattice constant, thermal expansion coefficient and specific heats at the constant volume of ZrO 2 thin films are calculated as a function of temperature, pressure and thickness of thin film. SMM calculations are performed using the Buckingham potential for the ZrO 2 thin films. In the present study, the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…In [196], the atomistic moment method in statistical (SMM) [197] dynamics was applied to investigate the thermodynamic properties of ZrO 2 thin films. It was revealed that the thermal expansion coefficient decreases with an increase in pressure and grows with an increase in the temperature and thickness.…”
Section: Kinetics Thermodynamics and Other Propertiesmentioning
confidence: 99%
“…In [196], the atomistic moment method in statistical (SMM) [197] dynamics was applied to investigate the thermodynamic properties of ZrO 2 thin films. It was revealed that the thermal expansion coefficient decreases with an increase in pressure and grows with an increase in the temperature and thickness.…”
Section: Kinetics Thermodynamics and Other Propertiesmentioning
confidence: 99%
“…is the Planck constant, ω is the vibration frequency of atom at lattice point node, k, γ 1 , γ 2 are parameters of the metal [38,39]. The cohesive energy u 0 the parameters k, γ 1 , γ 2 and γ for cubic metals in the approximation of two coordination spheres have the forms as in [38,39] The state equations for cubic metals are determined by [38,39,47]…”
Section: Theoretical Modelmentioning
confidence: 99%
“…This is the nearest neighbor distance between two atoms r 01 (P,0) at pressure P and temperature 0K. From that, we can determine the displacement of atom from the equilibrium position y(P,T) and the nearest neighbor distance between two atoms r 1 (P,T) at pressure P and temperature T [38,39]      …”
Section: Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations